Recognition of Omitted Intangible Assets : Risks and Rewards - Dobrotková, Kamila; Zelenka, Vladimír, 1961-; Svačina, Pavel, 1979-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2015)
The aim of this thesis is to analyse the research area of omitted intangible assets from the balance sheet and consider rewards of their potential recognition in the statement of financial position. The theoretical part provides the reader with the current regulation in force and compares it to the regulation prior the standardization and convergence process. The empirical part focuses on valuation of equity of three companies from the pharmaceutical industry based on the model pursued by American professor Stephen Penman. The values obtained are subsequently compared to market prices which are believed to reflect also the possession of omitted intangible assets. Differences identified speak in favour of potential recognition, however these are believed to be marginal comparing to probable inherent risks, which include, inter alia, stock market run-ups and earnings management.
Vedoucí práce: Vladimír Zelenka
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: účetnictví a finanční řízení podniku [obor dipl. práce]; diplomové práce; master's theses